Effects of Cardiopulmonary Exercise Rehabilitation on Left Ventricular Mechanical Efficiency and Ventricular‐Arterial Coupling in Patients With Systolic Heart Failure. Issue 10 (13th October 2015) - Aslanger, Emre; Assous, Benjamin; Bihry, Nicolas; Beauvais, Florence; Logeart, Damien; Cohen‐Solal, Alain
Abstract : Background: Success of cardiac rehabilitation (CR) is generally assessed by the objective improvement in peak volume of inhaled oxygen (VO2 ) measured by cardiopulmonary exercise test (CPX). However, cardiac mechanical efficiency and ventricular‐arterial coupling (VAC) are the other important dimensions of the heart failure pathophysiology, which are not included in CPX‐derived data. The effect of cardiac rehabilitation on left ventricular (LV) efficiency or VAC in unselected heart failure patients has not been studied thus far. Methods and Results: Thirty patients with an ejection fraction of ≤45% were recruited for 20 sessions of exercise‐based CR. Noninvasive LV pressure‐volume loops were constructed and VAC was calculated with the help of applanation tonometry and echocardiography before and after CR. VAC showed an improved mechanical efficiency profile and increased significantly from 0.56±0.18 to 0.67±0.21 ( P =0.02). LV mechanical efficiency improved from 43.9±9.1% to 48.8±9.1% ( P =0.01). The change in peak VO2 was not in a significant correlation with the change in VAC ( r =−0.18; P =0.31), mechanical efficiency ( r =−0.16, P =0.39), or the change in ejection fraction ( r =−0.07; P =0.68). Conclusions: CR is associated with an improvement in VAC and LV mechanical efficiency in heart failure patients. Further studies are needed to determine the incremental value of VAC and mechanical efficiency over CPX‐derived data in predicting clinical outcomes.